Association between DNA Damage and Serum Levels of Copper, Zinc, and Selenium in Full-Term Neonates with Late-Onset Sepsis - Wahby, Aliaa Ahmed; Elwassif, Maha; Magdy, Mai; Hamid, Tamer A. Abdel; Ibrahim, Alshaymaa A. (Journal of Pediatric Infectious Diseases, 2020)
Objective The alteration in certain trace elements is usually associated with impaired immune function and higher oxidative stress. Therefore, these elements are suggested to play an important role in the pathogenesis of neonatal sepsis. We aimed to evaluate copper (Cu), zinc (Zn), and selenium (Se) serum levels in full-term neonates with late-onset sepsis (LOS) and correlate these levels with DNA damage and other risk factors of sepsis.Methods The study included a group of 100 neonates diagnosed with sepsis serving as the case group and another one of 60 neonates serving as the control group. DNA damage was assessed using the comet assay method and trace elements were measured using inductively coupled plasma mass spectrometry.Results Compared with controls, the percentage of DNA damage was significantly elevated in patients with sepsis, while serum levels of Cu, Zn, and Se were markedly decreased (p = 0.001). A strong negative correlation was revealed between Se and DNA damage (r = −0.6, p = 0.001). However, no correlations were found between Cu or Zn and DNA damage. Univariate logistic regression analysis revealed that DNA damage as well as Cu, Zn, and Se serum levels can be considered as relevant risk factors for neonatal sepsis (p = 0.008, 0.004, 0.004, and 0.003, respectively). Receiver-operating characteristic curve analysis showed that the strongest indicator for neonatal sepsis was Se (area under the curve [AUC] = 0.94, confidence interval [CI] = 0.9–0.98, p = 0.001), followed by Cu (AUC = 0.9, CI = 0.85–0.96, p = 0.001), and then Zn (AUC = 0.87, CI = 0.8–0.93, p = 0.001).Conclusion The percentage of DNA damage may help in the assessment of neonatal sepsis severity. Altered levels of Cu, Zn, and Se may play significant role in the pathogenesis of neonatal sepsis. Se serum level is strongly correlated with percentage of DNA damage. Therefore, Se can predict the severity of LOS.
Keywords: copper; zinc; selenium; DNA damage; sepsis; late-onset sepsis